Clinical characteristics and prognostic factors of COVID-19 in rheumatic patients and their family members: a retrospective study - Fan, Yihua; Wang, Yiwen; Du, Juanli; Wu, Rui; Li, Jianbin; Xiao, Changhong; Li, Qing; Zhou, Mi; Liu, Ying; Zhang, Di; Wang, Bei; Li, Songwei; et al. (Frontiers in Immunology, 2024)
BackgroundPatients with rheumatic diseases who receive long-term treatment with steroids, immunosuppressants, or biologics are more susceptible to infection with pathogens than the general population. In order to explore the differences in clinical features and prognosis of Corona Virus Disease 2019 (COVID-19) infection between patients with rheumatic diseases and the general population (family members), a retrospective investigative study was used to analyze the differences between the two populations.MethodsThe study was conducted in 13 Grade A Tertiary hospitals in China to investigate the clinical symptoms and prognostic factors of patients with rheumatic diseases who were infected with COVID-19 for the first time and their families.ResultsA total of 2,889 participants were included in this study, including 1,530 patients with rheumatic diseases and 1,359 family members. In terms of clinical symptoms, the complete recovery time from COVID-19 for patients with rheumatic disease patients was 13 days (8.00, 18.00), which was shorter than that of family members (16 days, 11.00, 20.00). The risk of developing moderate to severe cases of COVID-19 was lower in patients with rheumatic disease than in their family members (OR=0.511, P=0.0026). Compared with non-use of non-steroidal anti-inflammatory drugs (NSAIDs), the risk of developing mild cases of COVID-19 was 0.595 times greater with pre-infection use of NSAIDs (P = 0.0003). The use of glucocorticoids and Chinese herbal decoctions before infection increased the probability of developing mild cases of COVID-19 (OR=1.537, 1.773, P<0.05). The risk of developing moderate to severe cases with disease-modifying anti-rheumatic drugs (DMARDs) used before infection was 0.350 times that without such drugs (P<0.001). In terms of prognosis, compared with family members, the complete recovery time of patients with rheumatic diseases was reduced by 2.241 days on average (P<0.001), and the complete recovery time of patients with mild rheumatism was reduced by 4.178 days on average (P<0.001). There was no significant difference in the complete recovery time from COVID-19 in patients with severe rheumatism compared with their family members (P=0.1672). The use of NSAIDs, glucocorticoids, DMARDs, biologics, Chinese patent medicine, and Chinese herbal decoctions during the infection period could shorten the recovery time of COVID-19 symptoms (P<0.05).ConclusionsCompared with their family members, patients with rheumatic diseases had milder symptoms after infection with COVID-19, which was related to the use of glucocorticoids, DMARDs, and Chinese herbal decoctions before infection. During the COVID-19 infection phase, the use of NSAIDs, glucocorticoids, DMARDs, biologics, Chinese patent medicine, and Chinese herbal decoctions might shorten the recovery time from symptoms of COVID-19.Chinese clinical trial registryChiCTR2300072679